The Mediating Role of Brand Awareness and Customer Satisfaction in the Relationship Between Brand Image, Service Quality, Product Quality, and Customer Loyalty - Riski Sugiarti; Ida Bagus Cempena; Estik Hari Prastiwi (International Journal of Economics (IJEC), 2026)
This study examines the influence of brand image, service quality, and product quality on customer loyalty through the mediating roles of brand awareness and customer satisfaction at PT Kao Indonesia Surabaya. Using a quantitative causal approach, data were collected from 260 customers through structured questionnaires. The analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that brand image, service quality, and product quality have direct positive and significant effects on customer loyalty. Brand awareness significantly mediates the relationship between brand image and customer loyalty. However, customer satisfaction does not mediate the brand image-loyalty relationship due to the pragmatic characteristics of fast-moving consumer goods (FMCG) consumers who prioritize functional product performance over abstract brand prestige. Both brand awareness and customer satisfaction significantly mediate the effects of product quality and service quality on customer loyalty. These findings contribute to marketing theory by demonstrating that in low-involvement product categories, cognitive brand recall dominates loyalty formation compared to satisfaction-based pathways. Practical implications suggest that FMCG companies should prioritize product quality consistency and service excellence over abstract brand image campaigns to maintain sustainable customer loyalty